Pripomočki za učinkovito hranjenje - Korelc, Simona (Rehabilitacija (Ljubljana), 2019)
Eating is an essential survival skill for every human being. Feeding and swallowing disorders in children and adults relate to malnourishment, aspiration and related problems with respiratory system, and thus higher risk of unsafe swallowing. Effective eating and drinking in patients with feeding and swallowing disorder depends on timely and appropriate characterisation of the problem and further multidisciplinary program. Professional (re)habilitation teams from the University Rehabilitation Institute in Ljubljana are included in the clinical assessment and treatment of children and adults. Feeding and swallowing function optimisation and provision of appropriate aids are a crucial part of the program, as the individualised treatment establishes conditions for safe swallowing and encourages eating independence.
Keywords: aids; eating disorders; motnja hranjenja; motnje požiranja; multidisciplinary team; Orthotic Devices; pripomočki; swallowing disorder; timska obravnava